A pair of metal organic framework (MOF)-derived oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) catalysts for zinc-air batteries. (June 2020) - Agarwal, Soham; Yu, Xingwen; Manthiram, Arumugam
Abstract: Metal organic frameworks (MOFs) are amazing precursors for the development of functional catalysts due to their ability of being modified both structurally and in terms of composition. This work presents a pair of MOF - derived oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) catalysts for the advancement of zinc-air batteries. Zeolitic imidazolate frameworks (ZIF) are known as ideal materials to create doped carbons. Combining with a sacrificial tellurium template, we have developed a "pseudo-carbon nanotube" with a ZIF-8 that is doped with a mixture of zinc, cobalt, and iron. The resulting mixed-metal doped porous carbon nanotubes (CoFeZn@pCNT) show excellent catalytic activity for ORR with a half-way ORR potential ( E 1/2 ) of 0.87 V vs. RHE (reverse hydrogen electrode). Iridium-based catalysts are known as the best option for OER so far, but it is not viable for practical applications due to cost restrictions. Previous research into alternative catalysts has focused on metal oxides with first-row transition metals. Metal sulfides provide superior conductivity compared to metal oxides and are a new frontier in the search for affordable, active, and stable OER catalysts. By combining cobalt, iron, and nickel into a MOF structure (ZIF-67), followed by a sulfurization process, a MOF-derived mixed-metal sulfide catalyst (FeCoNi–S@ZIF) has been developed in this study. The resulting catalysts show an onset OER potential of 1.65 V vs. RHE at 10 mA cm −2 and exhibit remarkable stability for the operation of zinc-air batteries. Graphical abstract: Image 1 Highlights: An active ORR catalyst has been developed with a MOF-combined sacrificial Te template. A MOF-derived mixed-metal sulfide OER catalyst shows high activity and stability. A Zn-air battery with a decoupled ORR/OER catalyst pair shows high energy efficiency.